Exploring consumer preferences and policy implications in local food systems: Does taste or labeling matter in honey? - Belinda Lopéz-Galán; Tiziana de-Magistris (Agricultural and Food Economics)
Abstract This study analyses the influence of geographical origin and taste on honey consumer behavior. First, we explore the influence of geographical origin on consumers’ hedonic evaluation of honey. We then assess the influence of geographical origin and taste on their willingness to pay (WTP) for honey. We conducted a field experiment at a real supermarket. The participants were exposed to two treatments (blind and informed treatment). The findings showed that knowledge about the geographical origin of honey influences consumers’ hedonic evaluations and that the WTP for honey is more strongly influenced by geographical origin than by taste.